Viable blastocystis cysts in scottish and Malaysian sewage samples - Suresh, K.; Smith, H.V.; Tan, T.C. (2005)
Blastocystis cysts were detected in 38 (47/123) (37 Scottish, 17 Malaysian) of sewage treatment works. Fifty percent of influents (29 Scottish, 76 Malaysian) and 28 of effluents (9 Scottish, 60 Malaysian) contained viable cysts. Viable cysts, discharged in effluent, provide further evidence for the potential for waterborne transmission of Blastocystis.